Exploring hidden potential: new strategies in women's cricket by examining muscle explosive intensity and eye-hand balance - Camelisa, Reffie; Bafirman, Bafirman; Syahrastani, Syahrastani; Zarya, Fiky (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
The aims of this study was to determine the relationship of grip strength and arm muscle strength to batting skills. This type of research is correlational. The population in this study was the West Sumatra women's Pre-PON cricket team which amounted to 14 people using total sampling technique where the population in accordance with certain requirements to be sampled, to obtain research data used two-hand medicine ball putt test, tennis ball throwing catch test and batting test. The data obtained were analyzed by product moment and double. The results showed that: 1) arm muscle explosive power has a significant relationship with the batting skills of the West Sumatra women's Pre-PON cricket team. 2) eye-hand coordination has a significant relationship with the straight drive of the West Sumatra women's Pre-PON cricket team. 3) arm muscle explosive power, eye-hand coordination has a significant relationship with the straight drive of the West Sumatra women's cricket team.